Sensing the Future: A Qualitative Synthesis of How Employees’ Technological Sensing Capabilities Shape GenAI Capabilities and Innovative Work Behavior - Mia Christy Patricia; Novrizal (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2025)
This qualitative literature review synthesizes interdisciplinary research on how employees’ technological sensing capabilities shape generative artificial intelligence (GenAI) capabilities and innovative work behavior. Drawing on dynamic capabilities theory, microfoundations of sensing, and human–AI interaction literature, the review integrates findings from management, information systems, and innovation studies. The synthesis reveals that technological sensing—employees’ ability to identify, interpret, and anticipate emerging technologies—does not directly translate into innovation, but operates through the development of distinct GenAI capabilities. In particular, GenAI evaluation capability consistently emerges as a stronger driver of innovative work behavior than GenAI usage capability alone, as it enables critical judgment, contextualization, and creative recombination of AI-generated outputs. The review further highlights contextual moderators such as leadership support, task complexity, and organizational climate. Overall, the study advances theory by positioning individual sensing as a microfoundation of AI-enabled innovation and offers implications for organizations seeking to leverage GenAI beyond efficiency gains.